Strategi Peningkatan Kinerja Sistem Drainase yang Berkelanjutan di Jalan Suka Karya Kecamatan Tuah Madani Kota Pekanbaru - Achmad Rudi Haryadi; Imam Suprayogi; Budijono Budijono (Jurnal Zona, 2025)
The problem of flooding and waterlogging in the Suka Karya Street area, Tuah Madani District, Pekanbaru City, indicates that the drainage system is not performing optimally. This has a negative impact on community activities and accelerates damage to road infrastructure. This study aims to formulate a strategy to improve the performance of a sustainable drainage system through an evaluative approach and technical analysis. The methods used include field surveys, collection of rainfall data, channel capacity, and community participation. The results of the study indicate that the main factors causing the suboptimal drainage system are sedimentation, channel narrowing, and low public awareness in maintaining environmental cleanliness. The proposed strategies include increasing channel capacity, implementing an environmentally friendly drainage system (eco-drainage), routine maintenance, and community involvement in drainage management. With the implementation of this strategy in an integrated manner, it is hoped that a resilient, efficient, and sustainable drainage system will be created in the face of climate change and increasing urbanization